2014
DOI: 10.1097/hp.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characterization of Radiation Doses from External Exposures and Relevant Contributors in Fukushima Prefecture

Abstract: 1In areas contaminated by radioactive materials, well-designed dose assessment is necessary in order to protect people from radiation exposure and manage the exposure situation appropriately. Probabilistic dose assessment is a useful method for providing a more complete characterization of information on dose distributions in the population, and requires statistically characterized data on pathway-relevant contributors. The objective of this paper is to determine statistical features of contributors to externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 8 publications
6
29
0
Order By: Relevance
“…The measured ambient dose rate was in the range of 0.07–0.55 μSv h −1 inside houses and 0.07–1.76 μSv h −1 outside houses. The GM and GSD of those measured outside houses were 0.35 μSv h −1 and 1.70, respectively . This result does not contradict the results measured by Fukushima prefecture described in Section .…”
Section: Methodssupporting
confidence: 75%
See 4 more Smart Citations
“…The measured ambient dose rate was in the range of 0.07–0.55 μSv h −1 inside houses and 0.07–1.76 μSv h −1 outside houses. The GM and GSD of those measured outside houses were 0.35 μSv h −1 and 1.70, respectively . This result does not contradict the results measured by Fukushima prefecture described in Section .…”
Section: Methodssupporting
confidence: 75%
“…By contrast, if the measured individual doses are classified in terms of population groups, the ratio can be reduced to approximately 3 in case of the participants from the Fukushima City Office, the Senior Citizens’ Club, and the Contractors’ Association. Our previous study, in which we statistically analyzed individual doses measured from February to April 2012, suggested that the homogeneity requirement could be satisfied for these three population groups. However, even after the data were classified with respect to participant group, clear nonhomogeneity was found in individual doses received by participants in the Agricultural Cooperative population.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations